La fragmentación de lo público en la ciudad: organización socioespacial, marco institucional y sociabilidad urbana - Rodríguez Cortés, Luisa (2016)
The configuration of cities has invariably impacted the production of public dimension, both in its institutional meaning where the central axis is constituted by the State, as in its relational and spatial aspects. Given this scenario, it is pertinent to question how the public dimension is configured within the framework of today’s cities? This article aims to contribute answering this question by examining three dimensions that are basic in the public dimension of the cities: socio-spatial organization; institutional framework and urban sociability. For this, a theoretical review is made, taking as reference the case of Mexico City, with the aim of shedding light on the processes that mark the limits and contents of what we define as public. As a conclusion, it is argued that the public dimension is highly fragmented, as a result of the way the urban order is structured, the focused and unlinked actions from the governments and the limitations and difficulties for the encounter and dialogue between different.